Pengembangan sistem pengaturan kuat tekanan pada alat screen coating untuk membuat lapisan tipis berbasis arduino uno (Development of a pressure strength control system for screen coating tools to make thin films based on Arduino Uno) - Rahmatul Fitria; - Yohandri (PILLAR OF PHYSICS, 2019)
Thin layer is a layer made of very thin material with a scale between nano and millimeter. To get a good quality coating, there are several methods that can be used, one of which is the screen coating technique. Screen Coating technique is a coating technique by pouring percusor and then swept it using a rubber rack. In the Screen Coating technique, the size of the substrate used depends on the design made, so that the substrate can be larger than the size of the Dip Coating and Spin Coating substrate. Speed and pressure are very much against the coating produced and for the speed used by Arduino Uno. This research is an experimental study, while this study describes the design specifications and performance design of a Screen Coating tool. Performance specifications describe the performance of the screen coating, while the design specifications explain the accuracy and accuracy of the screen coating. The measurement technique used is direct and indirect measurement. Data obtained directly from the pressure, then data from indirect measurements obtained by analysis of the accuracy and accuracy of the pressure. Based on the results of research that has been done, obtained accuracy from a pretty good pressure with the largest percentage of 2% and an average accuracy of 99.01%. The accuracy of the pressure is quite good, with an average error percentage of 1.66% and an average accuracy of 99.2%.